Social entrepreneurship management: PKK moms' poverty alleviation strategy - Sudiantini, Dian; Priatna, Wowon; Meutia, Kardinah Indrianna (CV. BImbingan Belajar Assyfa, 2023)
The PKK women who are a part of this partnership program (PKM) are from the village of Rancanumpang Gedebage in Bandung City, West Java. First off, there is a serious lack of enthusiasm among PKK mothers. The motive in question is motivation for company management and entrepreneurship; they are also motivated to become employees of other parties who offer employment prospects. Lectures, talks, demonstrations, and questions and answers are the approaches employed. It is hoped that by taking part in this service project, PKK women in Rancanumpang Gedebage, Bandung City, West Java, will help to reduce poverty by contributing to the improvement of the family economy and by being able to make use of the local community by the idea of the social entrepreneur management strategy.